EVALUATING LARGE LANGUAGE MODELS FOR MEDICAL INFORMATION EXTRACTION: A COMPARATIVE STUDY OF ZERO-SHOT AND SCHEMA-BASED METHODS - Zakaria KADDARI; Ikram El HACHMI; Jamal BERRICH; Rim AMRANI; Toumi BOUCHENTOUF (Applied Computer Science)
This study investigates the application of large language models, particularly ChatGPT, in the extraction and structuring of medical information from free-text patient reports. The authors explore two distinct methods: a zero-shot extraction approach and a schema-based extraction approach. The dataset, consisting of 1230 anonymized French medical reports from the Department of Neonatology of the Mohammed VI University Hospital, served as the basis for these experiments. The findings indicate that while ChatGPT demonstrates a significant capability in structuring medical data, certain challenges remain, particularly with complex and non-standardized text formats. The authors evaluate the model's performance using precision, recall, and F1 score metrics, providing a comprehensive assessment of its applicability in clinical settings.